Comparative Analysis of Civil Law Liability Towards Consumers in Business Disputes - Ridho, Fajar Ainun; Dzaki, Asif; Masruroh, Ainul (Research Horizon, 2024)
This research aims to determine the relationship between violation of sales and purchase contracts and losses experienced by consumers and to analyze the comparison of civil legal liability towards consumers in business disputes using the ANOVA approach in cases of violations of sales and purchase contracts because violating sales and purchase contracts can cause losses to consumers. This research uses a quantitative research design. The population in this research are consumers who carry out buying and selling goods transactions in Indonesia. The sample was selected using purposive sampling and analyzed using simple linear regression analysis and coefficient of determination to determine the relationship between the variables studied. The research results show that there are significant differences between groups in sales and purchase contract violations which influence the losses experienced by consumers. The regression coefficient (β1) of 0.75 indicates that every 1 unit increase in sales and purchase contract violations will increase the losses experienced by consumers by 0.75 units. This research implies that breaches of sales and purchase contracts can cause significant losses for consumers. Therefore, efforts need to be made to increase awareness and seriousness of business actors in protecting consumer rights.